Endovascular Embolisation Using N-Butyl-2-Cyanoacrylate: An Effective Treatment Option for Uterine Artery Pseudoaneurysm in Postpartum Hemorrhage - Pothula, Venkatesh; Dhanasekaran, Jagadeesan; Nekkala, Jyothsna; Sekar, Sabarish; Joseph, Santhosh (Journal of Clinical Interventional Radiology ISVIR, 2022)
In this case series, we evaluated the efficacy and safety of uterine artery embolization (UAE) using N-butyl- 2-cyanoacrylate (NBCA)/glue for the treatment of uterine artery pseudoaneurysm (UAP). Here, we report 8 patients with uterine artery pseudoaneurysm, who underwent UAE using NBCA/glue. Angiograms and medical records were retrospectively analyzed to determine the technical success, clinical success, complications, average procedure time, the average duration of hospital stay after UAE. All patients were presented with secondary postpartum hemorrhage with hemodynamic instability. The technical and clinical success rates were 100%, respectively. The average procedure time was 21minutes and the average duration of hospital stay was 2.2 days. We did not encounter any major complications. Two patients following UAE were naturally conceived and delivered by repeat LSCS. UAE using NBCA/glue is a safe and effective treatment option for UAP in both hemodynamically stable and unstable patients.
Keywords: uterine artery embolization; NBCA; uterine artery pseudoaneurysm